Minimizing waste, maximizing sustainability: Analyzing collaborative practices implementation barriers in the agri-fresh produce industry - Santosh Anand; Mukesh Kumar Barua; Rajesh Katiyar; Rakesh Kumar Meet (Sustainable Futures)
The agri-fresh produce industry confronts problems in minimizing food waste and achieving supply chain sustainability due to its complicated structure and lack of stakeholder participation. Significant food waste at numerous supply chain stages undermines the triple bottom line (Society, economy and environment) and wastes resources. Stakeholder collaboration, research, and information exchange can all help to minimize waste and improve sustainability. This study identifies barriers to implementing collaborative practices through literature analysis and expert insights and categorizes them into seven dimensions: relationship management practice, contractual and economic practice, joint practice, technological and information sharing practice, relationships management practice, and supply chain design practice. Furthermore, the grey-Decision Making Trial and Evaluation Laboratory (grey-DEMATEL) and Analytic Network Process (ANP) were employed to develop an integrated framework that identifies interrelationships and prioritizes dimensions and attributes. The influence relationship diagraph helps decision-makers make policy recommendations by understanding the cause-effect interrelationships among the dimensions and their corresponding barriers. Finally, sensitivity analysis was performed to ensure that the results are robust and reduce decision-making biases.